(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
This article scientifically analyzes the socio-psychological determinants of violence against women in the family. The study highlights the psychological, economic, and social factors of domestic violence and its impact on women’s personality and family relationships. Physical, psychological, economic, and sexual forms of violence, as well as the causes of their occurrence, are examined. The article also substantiates the issues of victimization, social maladaptation, and secondary victimization resulting from domestic violence from a psychological perspective. In addition, legal reforms aimed at protecting women in Uzbekistan and socio-psychological mechanisms for preventing violence are analyzed.